1989
DOI: 10.1029/wr025i001p00029
|View full text |Cite
|
Sign up to set email alerts
|

The seepage exclusion problem for spherical cavities

Abstract: The quasi‐linear problem of water exclusion from, or entry into, spherical cavities from steady uniform downward unsaturated seepage is solved. Both exact solutions and simple asymptotic results are found. These are qualitatively similar to those given previously for circular cylindrical cavities, exhibiting such features as the dry shadow and the roof‐drip lobes. A major practical result of the analysis is the function ∂max(s), the dependence of the maximum potential (at the roof apex) on the dimensionless qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 6 publications
(3 reference statements)
1
41
0
1
Order By: Relevance
“…Detailed studies of the effects of the downward seepage rate, soil hydraulic properties, and the geometrical effects of cavity (and by implication, barrier) shape and size have been made. Philip et al [1989a] gave the analysis for circular cylinders, Knight et al [1989] gave the analysis for spheres, Philip et al [1989b] gave the analysis for parabolic cylinders and paraboloids, and Philip [1989a] gave the analysis for sloping cylinders of arbitrary cross section. Philip [1989b] gave asymptotic solutions for elliptic cylinders, spheroids, strips, and discs, and Philip [1990a] gave asymptotic solutions for ellipsoids with arbitrary axial ratios, the results depending primarily on curvature at the upstream stagnation point.…”
Section: Seepage Exclusion Analyses Relevant To Maximal Capillary Barmentioning
confidence: 99%
“…Detailed studies of the effects of the downward seepage rate, soil hydraulic properties, and the geometrical effects of cavity (and by implication, barrier) shape and size have been made. Philip et al [1989a] gave the analysis for circular cylinders, Knight et al [1989] gave the analysis for spheres, Philip et al [1989b] gave the analysis for parabolic cylinders and paraboloids, and Philip [1989a] gave the analysis for sloping cylinders of arbitrary cross section. Philip [1989b] gave asymptotic solutions for elliptic cylinders, spheroids, strips, and discs, and Philip [1990a] gave asymptotic solutions for ellipsoids with arbitrary axial ratios, the results depending primarily on curvature at the upstream stagnation point.…”
Section: Seepage Exclusion Analyses Relevant To Maximal Capillary Barmentioning
confidence: 99%
“…Philip and his colleagues (Knight et al, 1989;Philip, 1989a,b;Philip 1990;Philip et al, 1989a,b) reported analytical studies on the perturbation of vertical downward flow of water around cavities in unsaturated soils. Their work was concerned with the flow in 'Gardner' soils in which the hydraulic conductivity of unsaturated soils is described by an exponential function of the soil-water pressure.…”
Section: Introductionmentioning
confidence: 94%
“…Or and Gheuehei [ 19991 concluded that dripping is sensitive to the ambient water vapor pressure in an open cavity and is likely to occur only under very high vapor pressures close to saturation. Philip et al [1989aPhilip et al [ , 1989b, Knight et al [1989] and Philip [1989aPhilip [ , 1989bPhilip [ , 1990 were the first to address the capillary barrier problem as it directly relates to seepage into buried cavities. They developed several steady-state analytical solutions for various-shaped cavities buried in a homogeneous unsaturated porous medium and subject to a uniform, constantdownward percolation flux (&).…”
Section: Capillary Barriersmentioning
confidence: 99%